(untitled) (Journal of Oriental Studies, 2019)
As we all know, there are no young people who are not familiar with slangs, which are used by us almost every single day. Slang consists of a lexicon of non- standard words and phrases in a given language.Let’s talk about the classification of the slang of Chinese language. Common slangs are di- vided into four major groups: 1) Foreign words (lexis); 2) Words made by adding different lexical words together; 3) Abbreviation; 4) Modern words; Enhancement and enhancement of the vocabulary of the language through the extension of the vocabulary not only through its internal capabilities, but also by the ability to communicate without the help of other languages. Key words: slang, internet-system, сlassification.